2021
DOI: 10.1002/emp2.12439
|View full text |Cite
|
Sign up to set email alerts
|

Teaching emergency ultrasound to emergency medicine residents: a scoping review of structured training methods

Abstract: Background Over the past 2 decades, emergency ultrasound has become essential to patient care, and is a mandated competency for emergency medicine residency graduation. However, the best evidence regarding emergency ultrasound education in residency training is not known. We performed a scoping review to determine the (1) characteristics and (2) outcomes of published structured training methods, (3) the quality of publications, and (4) the implications for research and training. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 107 publications
(286 reference statements)
0
2
0
Order By: Relevance
“…Proctored bedside scanning as a mechanism, which incorporates the traditional apprentice-style education of clinical ultrasound within EM that learners have reported as most impactful, was reported by 93% of programs. 8,9 Other areas of success are the required attendance of a QA session, having dedicated ultrasound faculty within programs, and having training from internal sources that can be adapted to the individual learners.…”
Section: Discussionmentioning
confidence: 99%
“…Proctored bedside scanning as a mechanism, which incorporates the traditional apprentice-style education of clinical ultrasound within EM that learners have reported as most impactful, was reported by 93% of programs. 8,9 Other areas of success are the required attendance of a QA session, having dedicated ultrasound faculty within programs, and having training from internal sources that can be adapted to the individual learners.…”
Section: Discussionmentioning
confidence: 99%
“…Cadaver patients offer trainees an additional stepping stone to learn USGRA before performing blocks on a living patient. A prior scoping review found that cadaver-based education was relatively infrequently used in resident ultrasound education [10]. However, some studies have shown cadaver-based models to improve resident confidence in performing forearm, brachial plexus, and fascia iliaca nerve blocks [8,11].…”
Section: Discussionmentioning
confidence: 99%
“…Despite recommendations for the utilization of standardized assessment measures from multiple organizations, there are also practical reasons why checklists have not yet been incorporated more widely. 1,4,18 Checklist completion places an additional demand on already limited EUS faculty and resident education time.…”
Section: Reflec Tive Discussionmentioning
confidence: 99%